Novel insights into the enrichment of phenols from walnut shell pyrolysis loop: Torrefaction coupled fractional condensation. (15th July 2021) - Zhu, Xiefei; Luo, Zejun; Zhu, Xifeng
Highlights: Torrefaction was beneficial to the enrichment of phenols. The distillation residue in pyrolysis loop contributed to the enrichment of phenols. Torrefaction and pyrolysis loop both had a negative effect on pyrolysis efficiency. Phenols tended to be enriched in the second condensing stage. The relative increase in the enrichment of phenols was at least 109.44%. Abstract: Enriching high-value chemicals from the pyrolysis of agricultural and forestry waste is an efficient way to achieve sustainable development and large-scale application of biomass pyrolysis. Phenols, as important chemical raw materials, spices and food additives, have attracted widespread attention. Herein, a novel technical route of torrefaction pretreatment combined with fractional condensation in pyrolysis loop was proposed to enrich the phenols in liquid products. In this study, the enrichment of phenols from the pyrolysis loop of walnut shell under the combination of torrefaction and fractional condensation was explored using a fixed-bed pyrolysis reactor equipped with a three-stage condensation system. Simultaneously, the effects of torrefaction on feedstocks were investigated through a thermogravimetric analyzer based on the characteristics of feedstocks. The results showed that the torrefaction and pyrolysis loop had a negative impact on the pyrolysis efficiency and the yield of liquid products, while the change in the condensation efficiency depended on the combined effects of torrefaction and pyrolysis loop. In addition, phenols tended to be enriched in the second condensation stage, especially phenol, o-cresol, 4-ethylphenol. Importantly, torrefaction could significantly enrich phenols in the liquid products, and the enrichment of phenols is relatively increased by 109.44% at least. Moreover, the pyrolysis loop was also beneficial to the enrichment of phenols, which was at least 90% higher than that of walnut shell. This study provided a potential route to enrich high value-added products from the pyrolysis loop of lignocellulosic biomass.